Kissing loop-mediated fabrication of RNA nanoparticles and their potential as cellular and in vivo siRNA delivery platforms. (10th November 2021) - Kim, Kyoung-Ran; Kim, Junghyun; Mao, Chengde; Ahn, Dae-Ro
Abstract : Embedding the kissing loop sequences in the RNA strands generated by rolling circle transcription is an efficient way to prepare RNA nanoparticles having a size suitable for cellular uptake and tumor accumulation. Abstract : We describe an efficient method to condense RNAs into tightly packed RNA nanoparticles (RNPs) for biomedical applications without hydrophobic or cationic agents. We embedded kissing loops and siRNA in the RNAs to constrain the size of RNPs to ca. 100 nm, making them suitable not only for cellular uptake but also for passive tumor accumulation. The resulting RNPs were efficiently internalized into cells and downregulated the target gene of siRNAs. When intravenously injected into tumor-bearing mice, RNPs could also accumulate in the tumor. The reported fabrication method could be readily adopted as a platform to prepare RNPs for in vitro and in vivo delivery of bioactive RNAs.